POTENSI DAN KAJIAN TIMBULAN SAMPAH PEMUKIMAN DI KAWASAN KOTA BANJARBARU (STUDI KASUS KELURAHAN GUNTUNG MANGGIS) - Luh Putu Lilis Suliatini; Danang Biyatmoko; Udiantoro Udiantoro; Khairunnisa Khairunnisa (Universitas Lambung Mangkurat, 2013)
The purpose of this study was to analyze the potential of household waste generation in urban settlements smooth mangosteen, measure the density of household waste in urban settlements mangosteen smooth, determine the composition of household waste in urban settlements smooth mangosteen, analyzing the value of Recovery Factor (RF) of household waste settlements that can be recycled. The method used in this study is a survey method using questionnaires and community respondents in Manggis Village Guntung Banjarbaru City. Measurement of the amount of waste generation starts with determining the sampling site, the blunt Manggis Village. Retrieval based on the number of samples SNI 19-3964-1995 (National Standardization Agency, 1995) on the Sampling Method and Sample Measurement Generation and Waste Composition by simple random sampling, the sampling method of random members of the population, regardless of the strata in the population members (Riduwan, 2007), in this study the sampling time was 8 days in a row. Can result in waste generation residential households in the Village of mangosteen Guntung 157.77632 kg / capita. Waste density residential households in the Village Guntung get the mangosteen in the average yield of 92.2019 kg/m3 density. Composition of household waste in the Village Guntung mangosteen settlement can result in organic waste 71.4516%, followed by 11.3125% of plastic waste paper waste at 0.84587%, 0.80855% of glass waste, waste iron at 0, 55 977% and other waste of 7.46361%. Value Recovery Factor (RF) potential recycling 91.39% wet waste, plastic waste, waste iron, and 100.0% waste glass, waste paper and other garbage 0.000%.